Delayed drug-induced catatonia in an adolescent girl—clinical implications: a case report - Max Winerdal; Konstantinos Skordas; Anna Karin Lidehäll; Carin Wilhelmsdotter; Helena Strömbergsson (Journal of Medical Case Reports)
Abstract Background Catatonia is a potentially life-threatening condition that is characterized by psychiatric and motor disturbances, such as negativism, hypomotility, bradykinesia, and unusual movements. The diagnosis is based on clinical examination and occurs in both pediatric and adult patients and is associated with an increased mortality. Catatonia is associated with psychiatric illnesses such as schizophrenia, major depression, encephalitis, and bipolar disorder. The physiopathology of catatonia is complex and not fully understood. There is an ongoing debate in the medical community whether catatonia is an independent syndrome, or secondary to other mental illnesses. This case presentation is unique, as there are few reports describing cases of isolated catatonic syndrome in the absence of any other psychiatric or medical condition with a delayed onset caused by recreational drug abuse. Case presentation We present the case of a 17-year-old Caucasian athletic girl with no previous contact with child and adolescent psychiatry, nor any previous drug abuse. After recreational intake of drugs, there was a delay of approximately 7 days, before the patient searched care with symptoms that were at a later stage recognized as catatonia. Treatment with a high dose of lorazepam in combination with memantine and lithium resulted in a regression of the symptoms. After 6 weeks the patient could be discharged from the hospital almost fully recovered. Conclusions An acute onset of psychomotor symptoms without any previous history of mental illnesses must be addressed early as a potential catatonic syndrome. Delayed onset of catatonic symptoms after intake of drugs should not be overlooked, and we here suggest that mephedrone might be capable of inducing delayed catatonia. It is feasible to use memantine as an adjuvant to the treatment of catatonia in adolescents.